STUDY OF THE ACCURACY OF AN IMPROVED METHOD FOR CALCULATING THE DURATION OF GAS FLOW IN PISTON SEALS WITHOUT LUBRICATION - TYMOSHCHUK, OLEKSANDER; NEIMAK, VITALII; KOROTYCH, OLGA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Based on the use of the random field method, improved methods for calculating the duration of the flow of the working medium-gas in greaseless piston seals were developed to perform convenient practical calculation methods that will be used in mechanical engineering. The purpose of the work is to study the created improved methods for calculating the duration of the flow of the working gas flow in piston metal-polymer seals. The result of this work is the improvement of the practical method for calculating the duration of the flow of the working gas medium in piston seals, as well as the assessment of the accuracy of the developed method for use in design activities for the design of piston seals of compressor units. The article considers the elastic contact of a highly anisotropic polymer rough surface with a smooth metal surface. An improved formula for calculating the nominal contact pressure in the piston-cylinder interface has been developed, which is suitable for engineering practical calculations for any realistically possible ratios of the outer diameter of the piston and the inner diameter of the cylinder before assembly. The calculation of the duration of the working gas flow in the piston seal was made using the original Versuch 2 program [4]. An improved method for determining the duration of the flow of the working gas in the piston seal was tested. The studies were performed on 9 samples made of structural materials - flubon 20, vinyl plastic, and fluoroplastic 4, and demonstrated good accuracy of our method. The differences between the calculation results and the experimental results ranged from 5.96% to 15.37%.